2021
DOI: 10.3233/jad-210065
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Apolipoprotein E3 and Glucose Levels Are Associated in APOE ɛ3/ɛ4 Carriers

Abstract: Background: Altered cerebral glucose metabolism, especially prominent in APOE ɛ4 carriers, occurs years prior to symptoms in Alzheimer’s disease (AD). We recently found an association between a higher ratio of plasma apolipoprotein E4 (apoE4) over apoE3, and cerebral glucose hypometabolism in cognitively healthy APOE ɛ3/ɛ4 subjects. Plasma apoE does not cross the blood-brain barrier, hence we speculate that apoE is linked to peripheral glucose metabolism which is known to affect glucose metabolism in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Our cohort further included only eight APOE ε2 positive individuals whereof none were homozygous, mainly due to the in general low frequency of this genotype. Last, we were unable to test a potential influence of the body mass index (BMI), or cardiovascular risk factors, such as hypercholesterolemia, on plasma apoE levels and cannot rule out an effect of these although our previous findings in healthy APOE ε3/ε4 subjects suggested that there are no differences in plasma apoE levels between individuals with a pathological (> 25) versus normal BMI [ 101 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Our cohort further included only eight APOE ε2 positive individuals whereof none were homozygous, mainly due to the in general low frequency of this genotype. Last, we were unable to test a potential influence of the body mass index (BMI), or cardiovascular risk factors, such as hypercholesterolemia, on plasma apoE levels and cannot rule out an effect of these although our previous findings in healthy APOE ε3/ε4 subjects suggested that there are no differences in plasma apoE levels between individuals with a pathological (> 25) versus normal BMI [ 101 ].…”
Section: Limitationsmentioning
confidence: 99%
“…A study that exclusively utilized female mice found that, similar to the EFAD results described above, glucose tolerance was impaired by an obesogenic diet in ApoE3-expressing mice but not in ApoE4-expressing mice (Koren-Iton et al, 2020); the converse, with respect to ApoE4 variant, has been reported in males (Arbones-Mainar et al, 2010). One study utilized mass spectrometry to assess plasma ApoE3 and ApoE4 levels in heterozygous human subjects, finding that [Glc] b was inversely related to the levels of ApoE3 but not correlated with ApoE4 levels (Edlund et al, 2021). Our findings are consistent with a report of very mild effects of APOE ε4 on GTT in human subjects (Virtanen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…50 Among cognitively unimpaired older adults, APOE -ε4 allele dose relates to greater glucose hypometabolism in AD-related brain regions. 51 APOE- ε4 allele dose is associated with a more global pattern of glucose hypometabolism among individuals with AD, 16 and a lower ratio of peripheral APOE- ε3-to- APOE- ε4 among older cognitively unimpaired APOE- ε3 / ε4 heterozygotes has been associated with associated with lower regional cerebral glucose metabolism 52 and higher plasma glucose levels, 53 suggesting dosage of peripheral APOE isoforms may also influence central and peripheral glucose metabolism. OEF has been observed to be slightly lower per APOE- ε4 allele in cognitively unimpaired older adults, 3 and while that finding is not observed in the present study (data not shown), we exclusively observed OEF interactions with APOE- ε4 in additive genetic models.…”
Section: Discussionmentioning
confidence: 99%